Penyuluhan Budikdamber pada Kelompok Ibu Rumah Tangga di Kelurahan Huangobotu Kota Gorontalo - Nuriman A Anwar; Ayu Gusasi; Mutiara Pampaile; Intan Tri Tiansih Nuna; Sri Windiyati U Amati; Fatma Fatma; Ramdan Piu; Fahria Utami Thalib; Taufiq Abdullah (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Extension on Fish Cultivation in Buckets (Budikdamber) to groups of housewives aims to increase understanding, skills and independence in managing local resources to support family food security. This activity was carried out in Huangobotu Village, Dungingi District, Gorontalo City, using lecture, discussion and live demonstration methods. The material presented includes efficient fish cultivation techniques using buckets as a medium, as well as integration with plants as an integrated agricultural system. The results of the activity showed that participants had high enthusiasm in adopting this simple technology. In addition, they can manage fish and plant cultivation independently in the household environment, which can increase the fulfillment of family food needs. However, several challenges arise regarding water management and selecting appropriate fish feed. This program shows great potential in increasing food security, especially for housewives in urban areas with limited land. The long-term success of this program requires ongoing support in technical aspects and solving problems that arise during the implementation of Budikdamber. Through this program, it is hoped that a community will be created that is more independent in meeting the nutritional needs of the family, as well as playing a role in realizing family-based food security.